Effect of augmented distributed generation in distribution networks. (February 2020) - Anastasiadis, Anestis G.; Kondylis, Georgios P.; Vokas, Georgios A.
Abstract: This paper aims to study the effect of augmented Distributed Generation (DG) penetration in the basic indices of the distribution network (voltage, angle, power flow, thermal fatigue of cables). For this purpose, a realistic expansion of an existing distribution grid is considered, after looking up theoretically the basic principles of distribution grids and DGs. The case study grid is analyzed as to its basic indices depending on the level of penetration of distributed generation so as to find the necessary but also the optimal penetration. Subsequently, for every different penetration level, the key indices of the grid are discussed and it is estimated whether this specific level is technically sufficient. The optimum penetration level as well as Distributed Energy Resources (DER) hosting capacity is also discussed.